A rapid classification and identification method applied to the analysis of glycosides in Bupleuri radix and liquorice by ultra high performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. Issue 19 (27th August 2018) - Shan, Lanlan; Yang, Na; Zhao, Yiwei; Sheng, Xue; Yang, Shenshen; Li, Yubo
Abstract: Bupleuri radix and liquorice are commonly used as a hepatoprotectants. Their main effective ingredients are triterpenoid saponins. It is known that the saponins in liquorice and Bupleuri radix not only promote the metabolism of sugar and lipids but also have anti‐inflammatory functions and hepatoprotective effect. However, the complexity of these compounds results in difficulty in studying their pharmacodynamics and mechanism. In this study, glycosides were the main components that were identified and selected as the main research object. First, the mass spectrometry information of the main chemical components in liquorice and Bupleuri radix were collected from the literature. The characteristic fragments and neutral losses were summarized according to typical cleavage methods. Second, the samples were analysed using ultra‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry, and characteristic fragment filters and neutral loss filters were successfully applied to screen 18 saponins from Bupleuri radix and 23 saponins and nine flavonoid glycosides from liquorice. Rapid classification and identification of the main components in Bupleuri radix and liquorice were finally achieved. This method promoted the development of chemical components in Bupleuri radix and liquorice, and provided a new way for screening, classifying, and identifying target components in complex samples of metabolomics and pharmacokinetics.